Pelatihan Manajemen Pengelolaan Masjid Era Modern di Kecamatan Pangandaran: Mengokohkan Eksistensi dan Pelayanan Masjid: Modern Mosque Management Training in Pangandaran District: Strengthening the Existence and Service of Mosques - Abdullah, Mulyana; Fahrudin, Fahrudin; Faqihuddin, Achmad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Mosque management in the modern era demands extensive adaptation to long-established religious and community functions while introducing advanced technology integration to meet the continuously evolving needs and expectations of its congregation. This research focuses on the development and implementation of the training "Modern Mosque Management: Strengthening Existence and Service," aimed at enhancing the mosque administrators' abilities to manage religious and social activities more effectively. Through an approach of extension and training, this program teaches modern management principles and the use of technological tools like Google Workspace to enhance the operational efficiency of mosques. The results indicate a significant improvement in mosque management competence, as evident from the impressive N-Gain scores. These scores not only reflect an increase in participants' understanding of effective mosque management but also the practical skills acquired during the training. The conclusion of this study underscores the importance of well-designed training programs in preparing mosque administrators to meet the challenges of a dynamic and changing environment, and in supporting the strategic role of the mosque as a center of spiritual and social activities in the community.